Socio-Linguistic Study of National Apologies in Public Discourse - Fawzi Hussein, Taban Mohammed (Al-Adab Journal, 2020)
An apology is a formal and known acknowledgement that an individual uses when some individuals violate human rights, i.e., apologies emerge when human rights are violated for a reason or another.The national apology can be defined as the type of apology that is political, collective, and intrastate which a group of people offer to another by using an appropriate representation. Though the term ‘age of apology’ first emerged two decades ago, the term ‘national apology’, even with age, has continued to be one that is specifically analytically elusive.In contrast to interpersonal apologies that exist between individuals, a collective apology is constructed of and directed to definite communities. It is considered as political since it is made by/through political or social companies, institutions or organizations and for past wrongdoings of political characters.Using national apology, the speaker tries to be political in his/her speech to be able to achieve his/her aim of the communication. Using different strategies, one of them is national apology, the speaker tries to avoid FTA and get the acceptable response from the audience.The aim of this study is to analyze how the speaker uses the national apology in public discourse, the reasons, the constructions and the meaning of this kind of apologies. This study is concerned with investigating the social functions of national apologies.